Green Marketing and Sustainable Consumer Behavior: A Study on Repurchase Intentions of Muslim Fashion Buttonscarves in Jabodetabek - Lubis, Deni; Syifa Izzati Anzania Putri; Muhammad Shulthoni (Velocity: Journal of Sharia Finance and Banking, 2025)
This study investigates the impact of green marketing strategies, brand image, and brand trust on consumers' repeat purchase intentions concerning sustainable fashion products in Indonesia, focusing on Buttonscarves. In this context, green marketing strategies are considered a strategic approach that may influence consumer preferences and decisions regarding environmentally friendly products. The research aims to identify the characteristics of Buttonscarves consumers, examine the effects of variables such as environmentally friendly products, green products, green prices, and green promotions on repeat purchase intention, and assess the influence of brand image and brand trust on purchasing decisions. This study utilizes primary data collected through online questionnaires. The findings reveal that environmentally friendly products, green products, green promotions, and brand image significantly affect the repeat purchase intention of Buttonscarves products.